2020
DOI: 10.1021/acsami.0c16107
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Photocatalytic Application of Moisture-Stable Hybrid Lead-Free Perovskite

Abstract: The employment of hybrid perovskite MAPbX 3 (MA = CH 3 NH 3 + , X = Br or I) as photocatalysts in a photocatalytic hydrogen evolution reaction represents a promising approach to store solar energy. However, the toxicity of Pb makes these materials difficult to pass environmental evaluation while the intrinsic moisture sensitivity puts forward high anhydrous requirements in photocatalysts synthesis, storage, and application, which further reduces their service life. Herein, we demonstrate a hydrogen-bond-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 46 publications
3
43
0
1
Order By: Relevance
“…For example, non-hydrogen bonding donor groups should be used instead of −NH 3 + , −CNH 2 + , and −NH + to reduce the number of binding sites for external water molecules in the structure. [33] Another option is to employ aromatic hydrophobic cations in combination with a variety of noncovalent interactions to achieve a tight arrangement of the entire crystal structure to block the entry of water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, non-hydrogen bonding donor groups should be used instead of −NH 3 + , −CNH 2 + , and −NH + to reduce the number of binding sites for external water molecules in the structure. [33] Another option is to employ aromatic hydrophobic cations in combination with a variety of noncovalent interactions to achieve a tight arrangement of the entire crystal structure to block the entry of water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a zero-dimensional Bi-based perovskite ( (3-ethylbenzo[d]thiazol-3-ium) 4 Bi 2 I 10 ) with a band gap of 2.04 eV was synthesized by Li et al, which showed an excellent photocatalytic activity in an aqueous solution. 11 Malavasi et al synthesized DMASnBr 3 (DMA = dimethylammonium) with a band gap of 2.7−2.85 eV and applied it in a photocatalytic experiment to improve the hydrogen photogeneration of graphitic carbon nitride. 10 However, the band gap is not narrow enough to absorb more low-energy photons, and the underlying dynamic charge transport mechanism of perovskites in an aqueous solution is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of OIHP in the field of photoelectrochemical water splitting and photocatalysis has garnered increasing attention. , First, unlike traditional metal oxide photocatalysts, OIHP materials exhibit relatively narrower band gaps that broaden the absorption range for harvesting low-energy photons . Second, the band edges of many OIHPs can exhibit superior positions for hydrogen photogeneration and photodegradation of pollutants by adjusting the elementary composition and electronic band structure. , However, it is well known that the most interesting photocatalytic experiments such as splitting of water, reduction of CO 2 , and degradation of organics require water or alternative polar solvents, thereby rendering it difficult to use OIHP materials that perform excellently in solar cells for photoelectrochemical water splitting and photocatalysis. Therefore, developing water-stable and non-toxic OIHPs as photocatalysts to efficiently utilize solar energy is a challenging subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…199 Moreover, by replacing traditional protonated countercations with alkylated countercations in a Bi-based hybrid system, a zero-dimensional perovskite (3-ethylbenzo[ d ]thiazol-3-ium) 4 Bi 2 I 10 was grown, exhibiting excellent stability in photocatalytic H 2 evolution. 200 These studies illustrate that lead-free PMs are promising candidates for photocatalytic H 2 generation with a moderate heterostructure constructed. To see the difference more intuitively in photocatalytic H 2 evolution with these diverse PMs, the reported test conditions and performances of PMs for water splitting with different compositions or structures are summarized in Table 1.…”
Section: Application Of Perovskite Photocatalysismentioning
confidence: 89%